Camrelizumab in combination with apatinib in second-line or above therapy for advanced primary liver cancer: cohort A report in a multicenter phase Ib/II trial. Issue 3 (19th March 2021) - Mei, Kuimin; Qin, Shukui; Chen, Zhendong; Liu, Ying; Wang, Linna; Zou, Jianjun
Abstract : Background: Emerging clinical data suggest that an immune checkpoint inhibitor in combination with an antiangiogenic agent is a reasonable strategy for multiple malignancies. We assessed the combination of camrelizumab with apatinib in pretreated advanced primary liver cancer (PLC, cohort A) from a multicohort phase Ib/II trial. Methods: Patients with PLC after prior systemic treatment(s) were administered camrelizumab (3 mg/kg, once every 2 weeks) plus apatinib (125, 250, 375, or 500 mg; once per day) in a 3+3 dose-escalation stage and subsequent expansion stage. The primary endpoints were tolerability and safety of study treatment. Results: From April 2017 to July 2019, 28 patients (21 with hepatocellular carcinoma and 7 with intrahepatic cholangiocarcinoma) received camrelizumab plus apatinib. Two dose-limiting toxicities (both grade 3 diarrhea) were reported in the 500 mg cohort. Therefore, the 375 mg cohort was expanded. Of the 19 patients in the 375 mg cohort, dose reduction to 250 mg occurred in 8 patients within 2 months after treatment initiation. Of the 28 patients with PLC, 26 had grade ≥3 treatment-related adverse events, with hypertension being the most common (9/28). One treatment-related death occurred. The objective response rate was 10.7% (95% CI 2.3% to 28.2%). Median progression-free survival and overall survival were 3.7 months (95% CI 2.0 to 5.8) and 13.2 months (95% CI 8.9 to not reached), respectively. Conclusion: The combination of camrelizumab with apatinib had a manageable toxicity and promising antitumor activity in patients with advanced PLC. Apatinib at a dose of 250 mg is recommended as a combination therapy for further studies of advanced PLC treatment. Trial registration numbers: NCT03092895 .